2009
DOI: 10.1002/jrs.2334
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐depending Raman line‐shift of silicon carbide

Abstract: Silicon carbide (SiC) is often used for electronic devices operating at elevated temperatures. Spectroscopic temperature measurements are of high interest for device monitoring because confocal Raman microscopy provides a very high spatial resolution. To this end, calibration data are needed that relate Raman line-shift and temperature. The shift of the phonon wavenumbers of single crystal SiC was investigated by Raman spectroscopy in the temperature range from 3 to 112 • C. Spectra were obtained in undoped 6H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 27 publications
5
36
0
Order By: Relevance
“…We also tested the heating effect of laser power on presolar SiC Raman features and found that the power needs to be increased by at least a factor of 10 before the TO peak starts to show a systematic downward shift of 1−2 cm −1 , which is in good agreement with the Bauer et al. () results. It is noteworthy to point out that the small heating effect of laser power on the SiC Raman signal is mainly the result of the small absorption coefficient of SiC at 532 nm so that only a very small fraction of the laser energy is absorbed in the material.…”
Section: Experimental Methodssupporting
confidence: 86%
“…We also tested the heating effect of laser power on presolar SiC Raman features and found that the power needs to be increased by at least a factor of 10 before the TO peak starts to show a systematic downward shift of 1−2 cm −1 , which is in good agreement with the Bauer et al. () results. It is noteworthy to point out that the small heating effect of laser power on the SiC Raman signal is mainly the result of the small absorption coefficient of SiC at 532 nm so that only a very small fraction of the laser energy is absorbed in the material.…”
Section: Experimental Methodssupporting
confidence: 86%
“…4 shows the Raman spectra of 6H-SiC and porous samples in the 940-990 cm -1 range. The peak at 965 cm À 1 is related to the longitudinal optic (LO) mode of the A 1 symmetry of SiC [6]. This peak exhibited a large change after etching under different current densities.…”
Section: Resultsmentioning
confidence: 95%
“…14,15 Shifts are attributed to thermal expansion and the effect of phonon decay. For the zone-center E 2 vibration, a symmetric two-phonon decay has been applied to adequately describe the dependence from 20 to 350 K. 15 In this process, the initial phonon of energy ω 0 decays into two phonons each having energy ω 0 /2 and opposite momentum wavevectors…”
Section: Physical Basis Of the Temperature Dependencementioning
confidence: 99%
“…The full description in either Eq. (1) or (3) is necessary, although availability of the dependence across the low-temperature range 14,15 is helpful in determining the necessary constants. Better implementation of the linear model is expected when the k B T 0 > hcω 0 2 condition is met for the reference temperature.…”
Section: Physical Basis Of the Temperature Dependencementioning
confidence: 99%